Hybrid stepper motor and its controlling techniques a survey - Khan, Talha A.; Taj, Talha A.; Ijaz, Imran (Proceedings of the 2014 IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference : 3-5 February 2014, 2014)
This paper presents an overview of the stepper motor and its different types. The literature review is then carried out by highlighting the features of the stepper motor and then the types of the stepper motor are compared and discussed. The schemes of control theory for the controller of the stepper motor are also presented.